To What Extent and How Does CSR Contribute to Achieving the MDGs? The Case of the RSA Banking Sector - Msagha, Zipporah (2011)
This dissertation examines the extent to which CSR contributes to the achievement of the Millennium Development Goals (MDGs) within the banking sector in South Africa (SA).The institutions in SA were historically plagued with numerous injustices to the black population which were attributable to the adoption of apartheid. This contributed to and resulted in major inequalities in various sectors including education, economic status, skills set, leadership and so on.